The influence of content-relevant background color as a retrieval cue on learning with multimedia - Meusel, Felicia; Scheller, Nadine; Rey, Günter Daniel; Schneider, Sascha (Education and information technologies, 2024)
Color has been investigated as a signaling cue in multimedia learning environments, guiding the learner’s attention and as an emotional design element, increasing the learner’s motivation and, thus, improving learning outcomes. Retrieval cues (e.g., visual cues, odor, sound) facilitating memory retrieval have been primarily investigated in learning simple word lists. Contrary to additional retrieval cues, the background color is a component that is always present in multimedia learning environments. This study investigates if the background color of learning texts as retrieval cue can enhance learning and affect cognitive load and motivation. Hypotheses are formulated according to the Cognitive-Affective Theory of Learning with Multimedia (CATLM) and in the setting of context-dependent memory, specifically the Information, associated Context, and Ensemble Theory (ICE). A 2 (related vs. unrelated background color) × 2 (with vs. without colors in the learning test) -factorial between-subjects design with an additional control group was utilized. For the control group, the background of the learning texts and learning questions was white. In total, 191 native German speakers were randomly assigned to the five groups. The findings indicate that relying solely on the background color as a retrieval cue is insufficient. Instead of facilitating memory retrieval, the background color remains context information stored separately from the item information. However, the results should be approached carefully as learning outcomes may be subject to ceiling and floor effects.